Ocena tempa zmian kosztów produkcji drewna „przy pniu” i cen surowca drzewnego w latach 2001–2009 na przykładzie Regionalnej Dyrekcji Lasów Państwowych w Zielonej Górze - Adamowicz, Krzysztof; Kaciunka, Henryka (Leśne Prace Badawcze, 2014)
The rate of change in the cost of logged timber and prices of raw timber during the period, 2001-2009, was examined for the Regional Directorate of the State Forests in Zielona Góra. A logarithmic evaluation of average rate of change indicated that the rate of increase in timber harvest costs was higher than the rate of increase in the average price of raw timber and likewise the price of most log grades. The average increase in raw timber value was 2.51% annually. The price of low-diameter raw timber (slash) increased 8.61%, and the price of large-diameter timber increased 1.94% annually, while the price of large coniferous segments increased 1.75% and broadleaf segments increased 2.98% annually. At the same time, the timber logging costs increased more than the timber price, to 4.17%, or 4.19% when administrative costs related to timber logging are included.